Examınation of the Dynamic Relationship Between Poverty and Inequality: Evidence from Nigeria Micro Data - Edeme, Richardson Kojo; Ogbeide, Evelyn Osaretin; Innocent, A. Ifelunini; Ugwu, Sam (International Journal of Economics and Financial Issues, 2017)
A major challenge in both research and policy debate is the understanding of how inequality is related to poverty. Although several studies have shown that inequality plays significant role in the rising poverty, the degree of poverty in any country or region is a function of the extent of inequality in the distribution of their income. In line with this, Valentine (1968) in Bradshaw (2006) opined that the plain meaning of poverty is relative deprivation which is inequality. Conversely, Van der Berg (2003) argued that a society with high levels of poverty may still be experiencing lower levels of inequality and low poverty co-existing with inequality. Given this contradiction-prone evidence, this study investigates the dynamic relationship between poverty and inequality in Nigeria to ascertain if inequality is a determinant of poverty in a semi-macro panel dataset employing the Generalized Method of Moments (GMM) method of estimation using panel data in a four-year round. The result of the study suggests that both present level and past levels of inequality has a significant impact on poverty. It shows further that past levels of poverty positively impacted on the present level of poverty. In addition to unemployment and level of education captured by literacy rate are important factors to be considered in poverty reduction. A major policy implication of the above findings is that lowering the high rate of inequality is important for the reduction of poverty. Consequently, there is need to ensure equity in the distribution of income in the country especially in those states that have very high poverty rate. This can take the form of taxes and transfers using appropriate fiscal policy tools. Keywords: Poverty, Inequality, Dynamic Panel Data JEL Classifications: C22, C33, I32